Help Not Wanted! Examining Factors that Influence Help Acceptance. Issue 4 (7th August 2020) - Hetrick, Andrea L.; Mitchell, Marie S.
ABSTRACT: We predict that contextual attributes (i.e., employees' need for help) and offeror attributes (i.e., offeror's performance, political nature) indirectly influence employee help acceptance through employees' willingness to accept obligation and exploitation concerns (i.e., social loafing concerns, distrust). Study 1 is an experimental design and demonstrated that contextual and offeror attributes influence employees' willingness to accept obligation and exploitation concerns, but only the offeror attributes (i.e., offeror performance and political nature) indirectly influence help acceptance through willingness to accept obligation and exploitation concerns. Study 2 is a field study of working adults to test the predictions while controlling for the direct effect of coworker exchange on help acceptance. The results of Study 2 replicated the results from Study 1.